COVID-19 patients and sudden sensorineural hearing loss: a review - Swain, Santosh Kumar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Coronavirus disease-19 (COVID-19) is a new pandemic caused by SARS-CoV-2 virus. COVID-19 patients often present with respiratory symptoms and death is the possible outcome. The potentiality for neuro-invasion by the SARS-CoV-2 is currently a subject of great debate. However, there is a paucity of information regarding the impact of the SARS-CoV-2 on the nervous system at the present moment. The impact of the coronavirus on the auditory system is little mentioned in the literature. Sudden sensorineural hearing loss (SSNHL) is a rare symptom associated with COVID-19 infection. This hearing deterioration could be attributed to the damaging effects of viral infections on the outer hair cells of the cochlea but the exact mechanism is still unknown. Awareness about this non-specific presentation like SSNHL in COVID-19 patients is often a challenge to a clinician for early management. Early identification of the SSNHL may be helpful for the isolation of the patient and also protect their infectiousness in the early period to prevent the spread of the disease. Early identification of hearing impairment is also helpful for early medical treatment of SSNHL which can save the hearing. This article reviews the epidemiology, etiopathology, clinical presentations, investigations, and treatment of SSNHL in COVID-19 patients. This review article surely makes a baseline from where further prospective studies can be designed for this rare clinical entity in COVID-19 patients as there are not many studies are done.